Accelerate Building Strategic Agility for a Faster-Moving World - Kotter, John P. (Boston Harvard Business Review Press, 2014)
It?s a familiar scene in organizations today: a new competitive threat or a big opportunity emerges. You quickly create a strategic initiative in response and appoint your best people to make change happen. And it does?but not fast enough. Or effectively enough. Real value gets lost and, ultimately, things drift back to the default status.
Keywords: Organizational change